The Influence of Biology Learning Using Concept Attainment Model on Student’s Cognitive Learning Achievement - Yuliati Yuliati; Maridi Maridi; Mohammad Masykuri (Journal of Education and Learning (EduLearn), 2018)
This research aimed to find out the difference of cognitive learning achievement between students taught with Concept Attainment Model and those taught with Discovery Learning model. This study was a quasi-experimental research. The population of research was the 12th Science graders of SMAN 1 Karas of Magetan Regency in school year of 2016/2017. The sample was taken using cluster random sampling technique, consisting of two grades: the 12th Science 4 grade as the first experiment class using Concept Attainment Model and the 12th Science 3 grade as the second experiment class using Discovery Learning model. Technique of collecting data used was t-test technique for data of students’ cognitive learning outcome. Data analysis was carried out using unpaired two-sample variance analysis. The result of research showed there was a difference of cognitive learning outcome between the students treated with learning using Concept Attainment Model and those treated with learning using Discovery Learning. The cognitive learning achievement of students taught with Concept Attainment Model was higher than that of those taught with Discovery Learning.